Famine, affluence, and amorality - Sackris, David (Array, 2021)
I argue that the debate concerning the nature of first-person moral judgment, namely, whether such moral judgments are inherently motivating (internalism) or whether moral judgments can be made in the absence of motivation (externalism), may be founded on a faulty assumption: that moral judgments form a distinct kind that must have some shared, essential features in regards to motivation to act. I argue that there is little reason to suppose that first-person moral judgments form a homogenous class in this respect by considering an ordinary case: student readers of Peter Singer"s "Famine, Affluence, and Morality". Neither internalists nor externalists can provide a satisfying account as to why our students fail to act in this particular case, but are motivated to act by their moral judgments in most cases. I argue that the inability to provide a satisfying account is rooted in this shared assumption about the nature of moral judgments. Once we consider rejecting the notion that first-person moral decision- making forms a distinct kind in the way it is typically assumed, the internalist/externalist debate may be rendered moot.